Islamic bank financial performance is based on Islamic Corporate Social Responsibility, Islamic Corporate Governance and intellectual capital - Siti Murtiyanti (Islamic Accounting Journal, 2022)
Abstract            The background of this research is the bank as an institution that collects funds from the public and at the same time as an institution to channel funds. However, nowadays, banks need strategic steps to win the hearts of the people. Improving the financial performance of banks is one of the right steps. The purpose of this study is to determine the effect of ICSR, ICG, and IC on the financial performance of Indonesian Islamic commercial banks with NPF as the moderating variable. The data taken is from the annual financial reports published by each selected bank according to the criteria. The samples taken were 45 samples from 9 selected banks. The technique used to calculate how many populations are used is by using a purposive sampling technique with several criteria. The data that has been obtained is then processed using eviews 12. The analysis is carried out in the form of stationary test, panel data regression test, MRA interaction test, F test, T test, R2 test, classical assumption test. The test results simultaneously and partially independent variables ICSR, ICG, IC have a positive and significant effect on financial performance. However that changed after being moderated with NPF. Where ICSR, ICG, and IC have a negative and significant influence. The value of adjusted R-square, which is 94.56%, indicates that all independent variables can explain 94,56% of the variation in financial performance variables, besides the remaining 5,44% is explained by variables outside the model.  Keywords: ICSR, ICG, IC, financial performance, NPF AbstrakLatar belakang dari penelitian ini yaitu bank sebagai lembaga yang menghimpun dana dari masyarakat dan sekaligus sebagai lembaga untuk menyalurkan dana. Akan tetapi di masa sekarang ini bank perlu langkah strategis untuk mengambil hati masyarakat. Dengan meningkatkan kinerja keuangan bank merupakan salah satu langkah yang tepat. Tujuan penelitian kali ini untuk mengetahui pengaruh ICSR, ICG, dan IC terhadap kinerja keuangan bank umum syariah Indonesia dengan NPF sebagai variabel moderasinya. Data yang diambil yaitu dari laporan keuangan tahunan yang dipublikasikan oleh masing-masing bank terpilih sesuai kriteria. Sampel yang diambil sebanyak 45 sempel dari 9 bank terpilih. Teknik yang digunakan untuk menghitung berapa banyak populasi yang digunakan yaitu dengan menggunakan teknik purposiv sempling dengan beberapa kriteria. Data yang telah diperoleh kemudian di olah dengan menggunakan eviews 12. Analisis yang dilakukan berupa uji stasioner, uji regresi data panel, uji interaksi MRA, uji F, uji T, uji R2, uji asumsi klasik. Hasil uji secara simultan dan parsial variabel independent ICSR, ICG, IC berpengaruh positif dan signifikan terhadap kinerja keuangan. Akan tetapi hal itu berubah setelah dimoderasi dengan NPF. Dimana ICSR, ICG, dan IC memiliki pengaruh negatif dan signifikan. Besarnya nilai adjusted R-squared yaitu 94,56 % mengindikasikan seluruh variabel independen dapat menjelaskan 94,56 % variasi variabel kinerja keuangan, selain itu sisanya 5.44 % dijelaskan oleh variabel di luar model.Kata Kunci: ICSR, ICG, IC, Kinerja keuangan, NPF